2019
DOI: 10.1093/mnrasl/slz144
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the physics when modelling cold gas clouds in a hot plasma

Abstract: This paper aims at studying the reliability of a few frequently raised but not proven arguments for the modeling of cold gas clouds embedded in or moving through a hot plasma and at sensitizing modelers to a more careful consideration of unavoidable acting physical processes and their relevance. At first, by numerical simulations we demonstrate the growing effect of self-gravity on interstellar clouds and, by this, moreover argue against their initial setup as homogeneous. We apply the adaptive-mesh refinement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Such a result has not been observed in the clouds simulated by Heitsch & Putman (2009). In Sander & Hensler (2019) we have shown that self-gravity makes a distinct difference in the evolution of even homogeneous clouds with low densities and far below their Jeans masses.…”
Section: Modelmentioning
confidence: 61%
See 3 more Smart Citations
“…Such a result has not been observed in the clouds simulated by Heitsch & Putman (2009). In Sander & Hensler (2019) we have shown that self-gravity makes a distinct difference in the evolution of even homogeneous clouds with low densities and far below their Jeans masses.…”
Section: Modelmentioning
confidence: 61%
“…However, for later stages (> 40 Myr) differences become striking. Furthermore, in Sander & Hensler (2019) we have shown that self-gravity leads to a core-halo density profile even for resting (i.e. without dynamical interaction with the ambient medium) and initially homogeneous clouds with mass below their Bonnor-Ebert mass.…”
Section: Gravitational Collapsementioning
confidence: 89%
See 2 more Smart Citations
“…The mass of our cloud is an order of magnitude below its Jeans mass. Recently, however, Sander & Hensler (2019 showed that selfgravity can have a significant effect on clouds below the Jeans mass if they have a cuspy density profile. In that case, the self-gravity inhibits stripping such that the cloud loses gas more slowly but also decreases the efficiency of condensation lowering the overall amount of cold gas.…”
Section: Limitations and Missing Physicsmentioning
confidence: 99%